Beyond Aid : New Sources and Innovative Mechanisms for Financing Development in Sub-Saharan Africa - Ratha, Dilip; Mohapatra, Sanket; Plaza, Sonia (World Bank, Washington, DC, 2012)
Given Sub-Saharan Africa's enormous resource needs for growth, poverty reduction, and other Millennium Development Goals, the development community has little choice but to continue to explore new sources of financing, innovative private-to-private sector solutions, and public-private partnerships to mobilize additional international financing. The paper suggests several new instruments for improving access to capital. An analysis of country creditworthiness suggests that many countries in the region may be more creditworthy than previously believed. Establishing sovereign rating benchmarks and credit enhancement through guarantee instruments provided by multilateral aid agencies would facilitate market access. Creative financial structuring, such as the International Financing Facility for Immunization, would help front-load aid commitments, although these may not result in additional financing in the long run. Preliminary estimates suggest that Sub-Saharan African countries can potentially raise USD 1-3 billion by reducing the cost of international migrant remittances, USD 5-10 billion by issuing diaspora bonds, and USD 17 billion by securitizing future remittances and other future receivables. African countries that have recently received debt relief however need to be cautious when resorting to market-based borrowing.